2018
DOI: 10.1155/2018/6380463
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNAs as Biomarkers of Gestational Diabetes Mellitus: Updates and Perspectives

Abstract: Gestational diabetes mellitus (GDM) is defined as any degree of carbohydrate intolerance, with onset or first recognition during second or third trimester of gestation. It is estimated that approximately 7% of all pregnancies are complicated by GDM and that its prevalence is rising all over the world. Thus, the screening for abnormal glucose levels is generally recommended as a routine component of care for pregnant women. However, additional biomarkers are needed in order to predict the onset or accurately mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 96 publications
0
54
0
1
Order By: Relevance
“…Accumulating studies have suggested miRNAs are closely related to glycometabolic disorders including GDM by regulating placental immunity, pancreatic β cell functions, insulin sensitivity, and insulin resistance [14][15][16]. Circulating miRNAs contributing to tissue cross-talk have also been identified as potential biomarkers for GDM [17]. As a result, miRNAs are crucial for the development of GDM, but how specific miRNAs regulate placental immunity and glucose metabolism remains not much clear.…”
Section: Mediators Of Inflammationmentioning
confidence: 99%
“…Accumulating studies have suggested miRNAs are closely related to glycometabolic disorders including GDM by regulating placental immunity, pancreatic β cell functions, insulin sensitivity, and insulin resistance [14][15][16]. Circulating miRNAs contributing to tissue cross-talk have also been identified as potential biomarkers for GDM [17]. As a result, miRNAs are crucial for the development of GDM, but how specific miRNAs regulate placental immunity and glucose metabolism remains not much clear.…”
Section: Mediators Of Inflammationmentioning
confidence: 99%
“…However, most of microRNAs, which were the subjects of our interest, have not yet been observed by other investigators to be dysregulated in maternal circulation (peripheral blood, plasma, or serum samples) of women with clinically established GDM or before the onset of GDM [20,21,37,80,92,143,149,[172][173][174][175][176]. So, it is feasible that epigenetic profiles of a series of microRNAs have also been changing with time by force of various circumstances as a result of the interaction between genetic and environmental factors [177].…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, a set of circulating microRNAs associated with cardiovascular/cerebrovascular diseases (miR-16-5p, miR-17-5p, miR-20a-5p, miR-29a-3p, miR-125b-5p, and miR-195-5p) was reported by several independent studies [20,21,80,92,143,172,173] to be upregulated during various gestational ages in serum or plasma of mothers with already-diagnosed GDM or mothers who were destined to develop GDM later during pregnancy. The data resulting from these prenatally ongoing studies and interaction network analysis [20,21,80,92,98,125,143,172,173] may support our current finding referring to upregulated expression profile of these particular microRNAs in whole peripheral blood of women with a prior exposure to GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few years, efforts have been made to understand the role of ncRNAs in the regulation of glucose metabolism in GDM [74]. In this context, miRNAs were dysregulated in the plasma and placenta from women suffering from GDM and associated with pregnancy and birth-related outcomes [75]. Yan et al reported that circRNAs were aberrantly expressed in the placental villi of the GDM group compared to the control group [76].…”
Section: Gestational Diabetesmentioning
confidence: 99%